2020
DOI: 10.21037/atm.2020.01.97
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of chronic hepatitis B virus infection in patients with breast cancer in a hepatitis B virus endemic area

Abstract: Background: Except for hepatocellular carcinoma, chronic hepatitis B virus (HBV) infection has also been reported to be associated with increased morbidity and mortality of other cancers. However, the impact of chronic HBV infection on the prognosis of breast cancer (BC) remains unclear. Our study aimed to evaluate the prognostic value of HBV infection for BC in an endemic area of HBV in China.Methods: There was a total of 1,904 patients with early BC who underwent mastectomy or breastconserving surgery enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
1
5
0
Order By: Relevance
“… 38 , 40 China has the world’s highest rate of HBV infection, with an estimated 70 million HBsAg carriers and a prevalence of 5% to 6% in the general population. 41 , 42 The prevalence of HBsAg in patients with MBC was 8.5% in the current study, which was consistent with earlier studies that found 8–15% in breast cancer patients 16 , 43 , 44 and basically consistent with the general population in western China. 45 Our findings revealed that MBC was not associated with elevated prevalence of HBV infection, which was in line with previous studies that HBV was not a breast cancer risk factor.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“… 38 , 40 China has the world’s highest rate of HBV infection, with an estimated 70 million HBsAg carriers and a prevalence of 5% to 6% in the general population. 41 , 42 The prevalence of HBsAg in patients with MBC was 8.5% in the current study, which was consistent with earlier studies that found 8–15% in breast cancer patients 16 , 43 , 44 and basically consistent with the general population in western China. 45 Our findings revealed that MBC was not associated with elevated prevalence of HBV infection, which was in line with previous studies that HBV was not a breast cancer risk factor.…”
Section: Discussionsupporting
confidence: 92%
“… 43 Xiao et al demonstrated that chronic HBV infection predicts a worse prognosis in stage II/III BC patients, but not stage I BC. 16 However, Gao et al 52 and Yu et al 48 respectively found that HBV infection had no association with DFS and OS of breast cancer patients. In the present study, we found that HBV infection did not influence the survival of MBC, no matter in patients with de novo or relapsed metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, based on the collected data from northwest China, these patients include those with better economic status, medical insurance, and educational level, and mostly belonging to the higher-income population, while the data from southeast China, which is densely populated, showed both rich and poor patient distribution with a higher proportion of patients with hepatitis B, 31 which may lead to a low probability of LM in northwest China. Currently, a model based on treatment and prevention of complications has been considered an important strategy in medical practice to identify those most likely to benefit from treatment interventions and cure liver disease, the patients in our study were more likely to have variant potential etiology of LM with the residence of northwest-southeast differences in China 31 , 32 since concurrent liver-related disease could attribute to the LM. 33 35 Recent guidelines describe PR-tumors as having a unique molecular signature and therefore, possess a particular therapeutic response to ET compared with PR + BC.…”
Section: Discussionmentioning
confidence: 99%